2009
DOI: 10.1177/0010414009332129
|View full text |Cite
|
Sign up to set email alerts
|

Democratization as Deliberative Capacity Building

Abstract: Effective deliberation is central to democracy and so should enter any definition of democratization. However, the deliberative aspect now ubiquitous in the theory, practice, and promotion of democracy is generally missing in comparative studies of democratization. Deliberation capacity can be distributed in variable ways in the deliberative systems of states and other polities. A framework is described for locating and analyzing the contributions of its components and so evaluating the degree to which a polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
454
0
24

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(479 citation statements)
references
References 46 publications
1
454
0
24
Order By: Relevance
“…Participation through deliberative practices has taken many forms in the various spheres of social life, shaped by two theoretical strands of democratic theory: "deliberative democracy" and "participatory democracy". The deliberative approach, developed since 1980, is based on communication as a process that allows citizens to participate in the construction of the common good (Habermas, 1996;Cohen, 1997;Gutmann and Thompson, 2004;Dryzek, 2009). The latter is the so called "participatory" approach, whose origins date back to the intensification of globalization processes which led to a reformulation of several aspects of nation states, including decision-making processes (Santos, 2002).…”
Section: Civil Society's Involvement In Healthcare Systems: Potentialmentioning
confidence: 99%
“…Participation through deliberative practices has taken many forms in the various spheres of social life, shaped by two theoretical strands of democratic theory: "deliberative democracy" and "participatory democracy". The deliberative approach, developed since 1980, is based on communication as a process that allows citizens to participate in the construction of the common good (Habermas, 1996;Cohen, 1997;Gutmann and Thompson, 2004;Dryzek, 2009). The latter is the so called "participatory" approach, whose origins date back to the intensification of globalization processes which led to a reformulation of several aspects of nation states, including decision-making processes (Santos, 2002).…”
Section: Civil Society's Involvement In Healthcare Systems: Potentialmentioning
confidence: 99%
“…Dryzek has already suggested that a deliberative systems approach is suitable for analysing democratic transitions (Dryzek 2009). In what follows, we give shape and substance to this suggestion by outlining a framework for describing both the spaces where deliberation occurs and how those spaces relate to each other, aswell as for evaluating the extent to which inclusive and reasoned deliberation determines the outcomes of the transition process.…”
Section: Assessing Democratic Quality Deliberativelymentioning
confidence: 99%
“…Both groups thought that their focus so far had been too local and that they would benefit from leveraging higher-level institutions. These conclusions, drawn from the groups' use of Scale Perspectives, signified a different role for the tool than was initially intended-rather than being merely a tool for the collection and secondary analysis of societal perspectives on scale dynamics, the tool could function as a direct way to empower societal actors in their participation in governance across multiple levels and time frames (Dryzek, 2009;Ostrom, 2009). …”
Section: Scale Perspectives Versionmentioning
confidence: 99%